Gear up for Online Teaching: Challenges, and Solutions. - Syeda Zarreen Raza; Sanaa Ahmed; Ziyad Sanaullah; Shaur Sarfaraz; Zahid Ali Memon; Syeda Kausar Ali; Syed Tariq Rafi (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objectives: The objectives encompassed identifying the myriad challenges educators face, elucidating their coping strategies, examining the support systems in place, and evaluating the efficacy of the measures taken to address these challenges. Methods: Conducted at Jinnah Sindh Medical University from January 2021 to April 2021, the study employed a descriptive cross-sectional approach involving teaching faculty member's rom both constituent and affiliated institutions during the COVID locked down period. With a total faculty population of 200, a sample size of 124 was determined, utilizing a 95% confidence interval and a 5% margin of error. Convenience sampling facilitated the recruitment process, with Principals/Heads serving as conduits for disseminating information about the research and distributing the questionnaire. Leveraging Google Forms as the data collection tool, the questionnaire encompassed various dimensions, including consent, bio data, encountered technical difficulties, and the corresponding solutions implemented. Upon securing Institutional Review Board (IRB) approval (JSMU/IRB/2021/406), the questionnaire dissemination process commenced, underscoring the ethical considerations inherent in research involving human subjects. Results: Analysis of the gathered data, performed using SPSS version 18, revealed valuable insights from the 124 participating teachers. Noteworthy demographic trends emerged, with a predominance of female teaching faculty possessing postgraduate qualifications and boasting 5-10 years of teaching experience. Key challenges encountered during online teaching sessions centered around broad- band connectivity issues, inadequacy of devices for virtual instruction, and a perceived lack of requisite training. Mitigating these challenges necessitated concerted efforts, as evidenced by the pro- active interventions orchestrated by entities such as the Professional Development Center/Medical Education and the Information Technology department. Through targeted training initiatives and infra- structure enhancements, including broadband speed upgrades and the provision of essential gad- gets, faculty members were empowered to navigate the evolving landscape of online education. Conclusion: The study investigated the transition to online teaching among faculty members during the COVID-19 pandemic, revealing a predominantly female demographic with limited prior online teaching experience. Challenges included assessing student learning and addressing technological barriers, with solutions primarily stemming from professional development and personal technologi- cal investments.